In vitro characterization of pralidoxime transport and acetylcholinesterase reactivation across MDCK cells and stem cell-derived human brain microvascular endothelial cells (BC1-hBMECs). Issue 1 (December 2016) - Gallagher, Erin; Minn, Il; Chambers, Janice; Searson, Peter
Abstract Background Current therapies for organophosphate poisoning involve administration of oximes, such as pralidoxime (2-PAM), that reactivate the enzyme acetylcholinesterase. Studies in animal models have shown a low concentration in the brain following systemic injection. Methods To assess 2-PAM transport, we studied transwell permeability in three Madin-Darby canine kidney (MDCKII) cell lines and stem cell-derived human brain microvascular endothelial cells (BC1-hBMECs). To determine whether 2-PAM is a substrate for common brain efflux pumps, experiments were performed in the MDCKII-MDR1 cell line, transfected to overexpress the P-gp efflux pump, and the MDCKII-FLuc-ABCG2 cell line, transfected to overexpress the BCRP efflux pump. To determine how transcellular transport influences enzyme reactivation, we developed a modified transwell assay where the inhibited acetylcholinesterase enzyme, substrate, and reporter are introduced into the basolateral chamber. Enzymatic activity was inhibited using paraoxon and parathion. Results The permeability of 2-PAM is about 2 × 10−6 cm s−1 in MDCK cells and about 1 × 10−6 cm s−1 in BC1-hBMECs. Permeability is not influenced by pre-treatment with atropine. In addition, 2-PAM is not a substrate for the P-gp or BCRP efflux pumps. Conclusions The low permeability explains poor brain penetration of 2-PAM and therefore the slow enzyme reactivation. This elucidates one of the reasons for the necessity of sustained intravascular (IV) infusion in response to organophosphate poisoning.